Evaluating professionals’ adaptations before and after a decision support intervention “the Adaptation and Fidelity Tool” (A-FiT)—A longitudinal within-person intervention design - Johanna Zetterlund; Henna Hasson; Ulrica von Thiele Schwarz; Margit Neher; Emmie Wahlström (Implementation Research and Practice)
Background Implementing evidence-based interventions (EBIs) in practice requires balancing fidelity and adaptation to suit new contexts. Careful considerations are needed to maintain the core elements for effectiveness while ensuring fit with new contexts. The Adaptation and Fidelity Tool (A-FiT) intervention addresses this challenge by providing support for professionals using EBIs in the sustainment phase of implementation. This study evaluates the A-FiT intervention and examines how professionals delivering an EBI manage fidelity and adaptation during the sustainment phase of implementation, before and after the intervention. Method Short, structured interviews were repeatedly conducted with 14 professionals delivering an EBI ( n  = 127). Data was analyzed using deductive content analysis focusing on adaptation types, planning, intentionality, and fidelity consistency. The adaptations were counted and compared before versus after the A-FiT intervention using a chi 2 -test. Results The professionals made about the same number of adaptations before and after the A-FiT intervention. However, after the intervention, significant changes in the type and intentionality of the adaptations were observed. Changes in type consisted of fewer “removing,” “substituting,” and “integrating another framework” adaptations and more “loosening structure” and “departing from the intervention” adaptations. Regarding intentionality, fewer planned adaptations with the intention of improving the EBI effects were made, while adaptations made for practical reasons, both planned and unplanned, increased after the A-FiT intervention. No statistical change was found regarding fidelity consistency. Conclusions The findings indicate increased awareness about fidelity and adaptation among the group leaders, resulting in fewer planned adaptations to enhance program effects and more practical adaptations to address context challenges. The A-FiT intervention appears to help professionals in their management of fidelity and adaptations when delivering EBIs. The study underscores the importance of understanding adaptations in their context, purpose, and impact (intended and unintended) on the outcome/value.